Simultaneous Localization and Mapping for pedestrians using distortions of the local magnetic field intensity in large indoor environments - Robertson, Patrick; Frassl, Martin; Angermann, Michael; Doniec, Marek; Julian, Brian J.; Garcia Puyol, Maria; Khider, Mohammed; Lichtenstern, Michael; Bruno, Luigi (2013 International Conference on Indoor Positioning and Indoor Navigation : 28-31 October 2013, Montbéliard-Belfort, France, 2013)
We present a Simultaneous Localization and Mapping (SLAM) algorithm based on measurements of the ambient magnetic field strength (MagSLAM) that allows quasi-real-time mapping and localization in buildings, where pedestrians with foot-mounted sensors are the subjects to be localized. We assume two components to be present: firstly a source of odometry (human step measurements), and secondly a sensor of the local magnetic field intensity. Our implementation follows the FastSLAM factorization using a particle filter. We augment the hexagonal transition map used in the pre-existing FootSLAM algorithm with local maps of the magnetic field strength, binned in a hierarchical hexagonal structure. We performed extensive experiments in a number of different buildings and present the results for five data sets for which we have ground truth location information. We consider the results obtained using MagSLAM to be strong evidence that scalable and accurate localization is possible without an a priori map.